Mastering interest rate risk strategy : a practical guide to managing corporate financial risk - Macrae, Victor (Pearson Education, 2015)
Financial institutions, private and public companies and governments can lose vast amounts of money from even minor changes in interest rates. Because of this, complex financial instruments have been developed to mitigate these exposures. But what happens when organisations hedge themselves to ill-advised and ill-formulated financial management strategies? Based on a proven analytical method, Mastering Interest Rate Risk Strategy explains, step-by-step, how to set up and run a sound interest rate risk strategy. Influenced by the author's work with leading companies and tested with banks, the.